Penyesuaian Akademik Tahun Pertama Ditinjau Dari Efikasi Diri Mahasiswa - Ghufron, M Nur (IAIN Kudus, 2017)
The aim of the present study was to determine the relationship between self efficacy and academic adjusment. The respondent of this study were (N=66) first year students in the Department of Tarbiyah, Islamic State College in Kudus. The data collection techniques used in this study is a questionnaire, self-efficacy scale and academic adjustment scale. Data were analyzed by using correlation analysis. The results of the study showed that there was a positive significant relationship between self efficacy and academic adjustment.